Egalitarian dynamics: liminality and Victor Turner's contribution to the understanding of socio-historical process - Kapferer, Bruce; Gold, Marina (Egalitarianism, 2024)
"Liminality: the state of being 'betwixt and between' is one of anthropology's most influential concepts. This volume reconsiders Victor Turner's innovative extension of Arnold Van Gennep's concept of liminality from within the Manchester tradition of Social Anthropology established by Max Gluckman. Turner's work was grounded in ethnography and engaged with philosophical perspectives in varied socio-historical contexts, extending well-beyond the confines of the anthropology that initially inspired much of his work. Liminality has therefore become a concept with broad interdisciplinary reach. Engaging with topical issues across the globe - from neuroscience to open access publishing and refugee experiences in Europe - this volume launches Turner's fundamental work into the future"--